Prevalence and predictors of intention to quit tobacco smoking in smokers of rural area of North India (Haryana) - Khan, Zahid A.; Goel, Ridhima; Mukherjee, Anup K.; Khan, Tazeen (International Journal Of Community Medicine And Public Health, 2018)
Background: Intention to quit is a strong predictor of quitting tobacco smoking. Knowledge about factors determining intention to quit smoking is essential for the development of smoking cessation strategies. The objective of this study was to determine the predictors of tobacco smoking cessation among smokers of a rural area of Haryana. Methods: A cross-sectional study was conducted among 945 current tobacco smokers of a rural area of district Ambala of Haryana, India through an interviewer-administered questionnaire. The survey included questions pertaining to socio-demographic factors, smoking history, smoking practices, knowledge about smoking-related damage, perceived health status and intention to quit. Binary logistic regression was used to determine the predictors of intention to quit smoking among the study participants. Results: The intention to quit smoking was present in 52.4% smokers out of whom 41.4% had attempted to quit smoking during the past 1 year. Binary logistic regression analysis revealed educational status, the presence of trigger feelings (stress/frustration/loneliness) for smoking, more money spent on smoking, the presence of any health problem, health professional advice received and awareness of harmful effects of smoking as predictors of intention to quit smoking. Conclusions:The prevalence of intention to quit smoking among study participants is high but lower in comparison to developed countries. The predictors of quitting intention in the current study should be considered during designing of tobacco control programs and policies.